A Review of Queer Women in Modern Spanish Literature: Activism, Sexuality and the Otherness of the “Chicas Raras” - Maria Jesus Horta Sanz (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
Simón-Alegre, Ana I. & Lou Charnon-Deutsch (Eds.) (2022) Queer Women in Modern Spanish Literature: Activism, Sexuality and the Otherness of the “Chicas Raras”, New York, Routledge. ISBN: 978-036-75635-3-0